PEMBERDAYAAN GURU DALAM IMPLEMENTASI KURIKULUM 2013 DI SD NEGERI 1 DELANGGU - Asmawulan, Tri; Sarjono, Yetty; Narimo, Sabar (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2015)
This study aims to: 1) Describe the teacher profile in publicelementary school 1 Delanggu; 2) Describe the teacherempowerment in public elementary school 1 Delanggu; 3) Describethe implementation of Curriculum 2013 in public elementary school 1Delanggu.This research is qualitative. Informants in this study were principals and teachersin primary school 1 Delanggu. Data was collected through interviews,observation and documentation. Data analysis techniquesused in this research isthe analysis of interactive models, namely data reduction, data display andconclusion. Remedy to test the credibility of the data using triangulationtechniques.The results ofthis study: 1) Profile of teachers in primary schools 1 Delanggugood enough indicated by 80% of teacher education has met the qualifyingstandard. But in primary school 1 Delanggu not have teachers BK; 2) In terms ofempowerment, there is a lack of professional competence that teachers do not doresearch, as well as the teacher's ability to operate a computerless. There is alsoa shortage in teachers' personal competence a reless disciplined time; 3)Implementation of Curriculum 2013 in primary school 1 Delanggu in planninghave constraints on the availability of textbooks to support learning activities.While the implementation of primary school 1 Delanggu implement Curriculum2013 is not in accordance with the time scheduled by the government. Even so,primay school 1 Delanggu been able to implement Curriculum 2013 in thelearning processwell. For the evaluation, because the first year of implementingthe new curriculum in 2013, so it can not be evaluated as normative andsummative.